Astrocytes mediate the effect of oxytocin in the central amygdala on neuronal activity and affective states in rodents - Wahis, Jérôme; Baudon, Angel; Althammer, Ferdinand; Kerspern, Damien; Goyon, Stéphanie; Hagiwara, Daisuke; Lefevre, Arthur; Barteczko, Lara; Boury-Jamot, Benjamin; Bellanger, Benjamin; Abatis, Marios; Da Silva Gouveia, Miriam; et al. (Nature neuroscience, 2021)
Oxytocin (OT) orchestrates social and emotional behaviors through modulation of neural circuits. In the central amygdala, the release of OT modulates inhibitory circuits and, thereby, suppresses fear responses and decreases anxiety levels. Using astrocyte-specific gain and loss of function and pharmacological approaches, we demonstrate that a morphologically distinct subpopulation of astrocytes expresses OT receptors and mediates anxiolytic and positive reinforcement effects of OT in the central amygdala of mice and rats. The involvement of astrocytes in OT signaling challenges the long-held dogma that OT acts exclusively on neurons and highlights astrocytes as essential components for modulation of emotional states under normal and chronic pain conditions.